2020
DOI: 10.3389/fimmu.2020.568412
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia Virus Activation and Antagonism of Cytosolic DNA Sensing

Abstract: Cells express multiple molecules aimed at detecting incoming virus and infection. Recognition of virus infection leads to the production of cytokines, chemokines and restriction factors that limit virus replication and activate an adaptive immune response offering long-term protection. Recognition of cytosolic DNA has become a central immune sensing mechanism involved in infection, autoinflammation, and cancer immunotherapy. Vaccinia virus (VACV) is the prototypic member of the family Poxviridae and the vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 176 publications
(245 reference statements)
0
33
0
1
Order By: Relevance
“…Our results indicate that UBCv1 (I215L) is a new NF-ĸB modulator that cooperates with A238L. The presence of multiple viral proteins targeting the same innate immune pathway providing functional redundancy is not uncommon, and has been extensively reported for another large DNA virus such as VACV [ 39 , 41 , 42 , 43 ]. For instance, VACV protein A49 (used here as a control for NF-κB activation assays) acts at the level of IκBα degradation, blocking this by virtue of an N-terminal extension that mimics the IκBα phosphodegron recognised by the E3 ubiquitin ligase β-TrCP [ 30 , 34 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Our results indicate that UBCv1 (I215L) is a new NF-ĸB modulator that cooperates with A238L. The presence of multiple viral proteins targeting the same innate immune pathway providing functional redundancy is not uncommon, and has been extensively reported for another large DNA virus such as VACV [ 39 , 41 , 42 , 43 ]. For instance, VACV protein A49 (used here as a control for NF-κB activation assays) acts at the level of IκBα degradation, blocking this by virtue of an N-terminal extension that mimics the IκBα phosphodegron recognised by the E3 ubiquitin ligase β-TrCP [ 30 , 34 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 62%
“…For instance, VACV protein A49 (used here as a control for NF-κB activation assays) acts at the level of IκBα degradation, blocking this by virtue of an N-terminal extension that mimics the IκBα phosphodegron recognised by the E3 ubiquitin ligase β-TrCP [ 30 , 34 , 44 , 45 ]. Upstream of A49, several other viral proteins have the capacity to suppress NF-κB activation, acting at the level of TLR adaptors, TRAFs and IKK (reviewed in [ 41 , 42 ]). The value of encoding for these viral upstream inhibitory molecules is thought to confer a stronger immunomodulatory potential not only due to the cumulative action of these proteins on one pathway, but also on other crosstalking pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of cGAS, STING or TBK1 in cells results in reduction of activated IRF3, IRF3 responsive genes, STAT1 and STAT2 following exposure AdVs [ 228 ]. VV can replicate its DNA genome in the cytoplasm of infected cells and can suppress the innate immune response through the expression of multiple inhibitors acting upstream and downstream of the immune pathway, and thus block cytosolic DNA sensing, which was recently reviewed by El-Jesr et.al 2020 [ 229 ]. The host’s DNA sensing of VV is complex and hence an attenuated VV strain, such as MVA or genetically engineered mice is widely used to gain insights into VV immunity.…”
Section: Cyclic Gmp-amp Synthasementioning
confidence: 99%
“…Several studies indicated that type I IFN production by MVA is dependent of cGAS and its downstream adaptor STING [ 227 , 232 ]. Mice or human cells deficient in cGAS or STING show impaired production of type I IFNs in response to MVA [ 229 , 233 ]. Moreover, cGAS-deficient mice showed higher viral titer and greater susceptibility to VV (western reserve strain) [ 234 ].…”
Section: Cyclic Gmp-amp Synthasementioning
confidence: 99%
“…Unlike most DNA viruses that replicate inside the cell nucleus avoiding the hostile cytosolic environment, poxviruses, a large family of linear dsDNA viruses, complete their life cycle exclusively in the cytoplasm. Such a strategy requires poxviruses to encode effective immune evasion mechanisms that dampen cellular cytosolic DNA surveillance, and a number of these have been described [ 4 , 5 ]. Recently, the immunomodulatory capacity of poxviruses gained a new perspective with the discovery of a viral cGAMP nuclease termed poxin (poxvirus immune nuclease) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%